2009
DOI: 10.1103/physrevb.80.155429
|View full text |Cite
|
Sign up to set email alerts
|

Computational study of boron nitride nanotube synthesis: How catalyst morphology stabilizes the boron nitride bond

Abstract: All material supplied via Aaltodoc is protected by copyright and other intellectual property rights, and duplication or sale of all or part of any of the repository collections is not permitted, except that material may be duplicated by you for your research use or educational purposes in electronic or print form. You must obtain permission for any other use. Electronic or print copies may not be offered, whether for sale or otherwise to anyone who is not an authorised user. In an attempt to understand why cat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 95 publications
(210 reference statements)
4
15
1
Order By: Relevance
“…The same surface reconstruction is reported by Riikonen et al [17], who also allowed full relaxation of the top most layers. Using the PBE XC-functional, that is known to typically provide larger adsorption energies than the RPBE, these authors obtain adsorption energies of −6.6 eV and −6.3 eV for N on the quasi fourfold hollow site and on the threefold site, respectively.…”
Section: A N/fe(110) Pessupporting
confidence: 64%
See 2 more Smart Citations
“…The same surface reconstruction is reported by Riikonen et al [17], who also allowed full relaxation of the top most layers. Using the PBE XC-functional, that is known to typically provide larger adsorption energies than the RPBE, these authors obtain adsorption energies of −6.6 eV and −6.3 eV for N on the quasi fourfold hollow site and on the threefold site, respectively.…”
Section: A N/fe(110) Pessupporting
confidence: 64%
“…Molecular beam experiments directed to probe the dynamics of the N 2 /Fe(111) system showed that the N 2 translational kinetic energy can be efficiently used to promote reactivity on this surface [11]. The initial dissociative adsorption probability increases by a factor of 10 5 , rising from 10 −6 at 0.09 eV to 10 Interaction of N 2 with the less reactive Fe(110) has also attracted great interest [12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tungsten surfaces, among others, have received much attention [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], with particular focus on the large crystallographic anisotropy that this metal exhibits with respect to nitrogen adsorption. For instance, the thermal reactivity of W(100) is about two orders of magnitude larger than the W(110) reactivity [2].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic search to find the optimal adsorption sites for C atoms and C 2 molecules was performed on the slabs of Fig.1 along the lines of Ref. [33].…”
Section: B Technical Detailsmentioning
confidence: 99%